Rethinking Marriage Guardians for Widows in Indonesia : Perspective of Legal Certainty and Maslahah Theory - Ahmad Suryana; Khoirul Hidayah; Muhammad Muhammad (Justicia Islamica, 2025)
The issue of marriage guardianship (wali nikah) for widows remains crucial in Indonesia.  BPS 2022 data shows over 13 million widows (cerai mati) and 2.7 million divorced women (cerai hidup). He absence of explicit regulation in Article 14 of KHI creates legal uncertainty, often leading widows to unregistered marriages (nikah sirri), risking their legal protection and rights. It is at this point that the study of this article aims to examine more deeply the stipulation of the “marriage guardian” requirement for widows in the Compilation of Islamic Law, reviewed according to the theory of legal certainty and benefit. At the same time, this article also aims to identify and analyze the form of reformulation of the provisions of marriage guardianship for widows according to the theory of legal certainty and legal benefit. The research method used in this article is a qualitative prescriptive method with a normative juridical approach, utilizing legal interpretation and literature review. The findings indicate that Article 14 of the Compilation of Islamic Law does not explicitly regulate the marriage guardian for widows, causing legal uncertainty and increasing unregistered marriages (nikah sirri), which result in unclear legal status and administrative obstacles. The study recommends the reformulation of clear and fair provisions affirming the widow's authority in marriage, ensuring legal certainty and alignment with the principles of Islamic law and national legal norms. The contribution of this article lies in offering a specific legal reformulation of Article 14 of the KHI regarding the marriage guardian for widows.